A low bandgap polymer based on isoindigo and bis(dialkylthienyl)benzodithiophene for organic photovoltaic applications. Issue 1 (14th August 2012) - Cao, Kangli; Wu, Zhongwei; Li, Shugang; Sun, Baoquan; Zhang, Guobing; Zhang, Qing
Abstract A new conjugated polymer PBDTT‐ID based on N‐alkylated isoindigo (ID) and bis(2, 3‐dialkylthienyl)‐substituted benzo[1, 2‐b:4, 5‐b′]dithiophene (BDTT) as repeating units was synthesized. It had an optical bandgap of 1.56 eV and a highest occupied molecular orbital (HOMO) energy level of −5.71 eV. The optical, electrochemical, and photovoltaic properties of new polymer were compared with previous reported polymer PBDT‐ID, which was based on bis(alkoxy)‐substituted benzo[1, 2‐b:4, 5‐b′]dithiophene. The new polymer displayed lower HOMO energy level and better absorption properties than polymer PBDT‐ID. The solar cells fabricated with PBDTT‐ID/PC61BM (1:2, w/w) blends as active layers exhibited photoresponse in the range of 300–800 nm. A power conversion efficiency of 4.02% and an open circuit voltage (Voc) of 0.94 V were achieved in polymer solar cell device based on the new polymer. This was the highest Voc realized among the isoindigo‐based polymers. The relatively high performances of new polymer in solar cell devices were interpreted in terms of material properties and morphologies of polymer/PCBM blends. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013